Elevating the Antagonist Encounter: How the ‘Stitch’ Transforms Victimhood Contestation on TikTok - Marloes Geboers; Esther Hammelburg (Anglica. An International Journal of English Studies)
Working as speech acts that delineate online communities, claims to victimhood tend to evoke contestation. Their inherent political nature spurs user engagement in the shape of clicks, shares, emojis, and so on. TikTok’s multimodality has given rise to new practices of engagement that significantly shape how victimhood is communicated and negotiated. This study draws attention to the platform vernacular practice of the ‘stitch.’ Allowing users to respond to someone else by ‘remixing’ social media content of others, the stitch is a platform practice designed for commentary. We zoom in on stitched videos networked by hashtags, published in relation to the Israel-Hamas war. TikTok’s multimodality expands user pathways that connect claimants and those who contest them. Moving beyond hashtag hijacking the stitch elevates a practice of commentary that turns victimhood politics into a spectacle that politicizes formerly less political realms, and that further blurs the boundaries between on- and offline spaces. The analysis shows how stitched videos are especially used for antagonist encounters where they crowd out the ‘original’ post to which they respond. In this way, stitches can be seen as tools that aid platformed ‘regimes’ of visibility that prioritize the antagonist encounter in order to commodify them.